2021
DOI: 10.1101/2021.07.17.452778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HLA-dependent variation in SARS-CoV-2 CD8+ T cell cross-reactivity with human coronaviruses

Abstract: Pre-existing T cell immunity to SARS-CoV-2 in individuals without prior exposure to SARS-CoV-2 has been reported in several studies. While emerging evidence hints toward prior exposure to common-cold human coronaviruses (HCoV), the extent of- and conditions for- cross-protective immunity between SARS-CoV-2 and HCoVs remain open. Here, by leveraging a comprehensive pool of publicly available functionally evaluated SARS-CoV-2 peptides, we report 126 immunogenic SARS-CoV-2 peptides with high sequence similarity … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…NetCTLpan analysis of these human peptides showed that these self-peptides were predicted as T-cell epitopes with similar binding affinity to the HLA molecules that present the corresponding SARS-CoV-2 peptide (Table 7 compare with Table 4). SARS-CoV-2 peptides having high similarity to several human proteins have also been reported by other [63].…”
Section: Homology With Human Peptidessupporting
confidence: 60%
“…NetCTLpan analysis of these human peptides showed that these self-peptides were predicted as T-cell epitopes with similar binding affinity to the HLA molecules that present the corresponding SARS-CoV-2 peptide (Table 7 compare with Table 4). SARS-CoV-2 peptides having high similarity to several human proteins have also been reported by other [63].…”
Section: Homology With Human Peptidessupporting
confidence: 60%
“…A unique and valuable characteristic of this data megapool is that—with the exception of several peptides from other coronaviruses (e.g. MERS, SARS-CoV) which share homology with SARS-CoV-2 [ 27 , 28 ]—many of these peptides have not been used in the training data of the models under investigation ( Supplementary Fig. S1A available online at http://bib.oxfordjournals.org/ ) due to their recent identification.…”
Section: Resultsmentioning
confidence: 99%
“…15 Centre d'Investigation Clinique, INSERM CIC 1403, Centre Hospitalo universitaire de Lille, Lille, France. 16 INSERM UMR 1219, Bordeaux, France. 17 CHU Lille, Lille, France.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Moreover, more than 100 immunogenic SARS-CoV-2 peptides are highly similar to peptides from at least one human coronavirus (hCoV) presented by a wide range of classical HLA molecules 16 . We, therefore, tested the hypothesis of an association between HLA alleles and asymptomatic SARS-CoV-2 infection in two large independent cohorts.…”
Section: Introductionmentioning
confidence: 99%